Pengaruh Ekuitas Dan Liabilitas Terhadap Laba Bersih Pada PT BANK Muamalat Indonesia Tbk Periode 2014-2021 - Yufi Saputra; Titin Agustin Nengsih; Ahmad Syukron Prasaja (JOURNAL SAINS STUDENT RESEARCH, 2023)
This research is motivated by the discovery of problems in the financial statements of Bank Muamalat, which can be identified the main problem, namely Equity, Liabilities and Net Profit at PT Bank Muamalat Indonesia Tbk for the 2014-2021 period experiencing fluctuations. The aims of this study are: To determine whether equity and liabilities have a simultaneous and partial effect on net income at PT Bank Muamalat Indonesia Tbk for the 2014-2021 period. The subject of this research is the financial quarterly report of PT Bank Muamalat Indonesia Tbk for the 2014-2021 period. While the research method used in writing this thesis uses a quantitative approach using multiple regression statistical analysis methods to see the effect of equity and liabilities simultaneously and partially on net income at PT Bank Muamalat Indonesia Tbk for the 2014-2021 period. The results of this study are: partially Equity has no significant effect on the Net Profit of Bank Muamalat Indonesia for the period 2014-2021 while Liability has a significant effect on the Net Profit of Bank Muamalat Indonesia for the period 2014-2021. Simultaneously, Equity and Liabilities have a significant effect on the Net Profit of PT Bank Muamalat Indonesia Tbk for the 2014-2021 period.